Current Status of Calculating the Cost of Oilcrop Grains (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The current state of calculating the cost of oilseeds is of great importance in the agricultural sector. This process, by taking into account the costs of materials, labor and energy required for each crop, helps to increase production efficiency and improve economic results. Currently, it is necessary to apply international experience and new technologies, modernize calculation methods, as well as adapt them to local conditions.